Psychological Insights into Emotion-Based Brand Experience in the Context of Bakery Microenterprise - Atchchana, K.; Leo, C.A.; Hansamali, D.K.C.; Bulathsinghala, D.R.P.; Rajapaksha, I.S.; Perera, J.A.I.C.; Mahanama, M.P.P.I.; Abejayarathna, M.V.; Fernando, M.A.L.; Chathurika, W.A.H.; Dilogini, S. (Faculty of Management Studies | Rajarata University of Sri Lanka, 2025)
This study explores how emotions influence customer behaviour and loyalty in small bakery businesses in Northern Sri Lanka. Bakery microenterprises are an essential part of local economies and daily life in Northern Sri Lanka, yet little research has explored how emotions shape consumer experiences in these small-scale businesses. The objective of this study is to explore how emotion-based brand experiences influence customer behaviour and loyalty in bakery microenterprises. This study uses a qualitative approach based on consumer psychology. The researchers collected data through in-depth interviews with bakery owners and employees and through six focus group discussions with different consumer groups. These groups included loyal customers, first-time buyers, teenagers, parents and middle-aged individuals. Thematic analysis identified emotional comfort, emotional appeal, familiarity, and relationship warmth as key drivers of consumer loyalty. These factors often outweigh practical concerns such as price or product type. The findings indicate that emotional triggers such as the smell of bakery products, attractive visuals, nostalgic memories and friendly human interactions greatly influence customer experiences. Loyal customers appreciate routine and familiarity. Teenagers associate bakeries with social interactions. Parents look for products that will delight their children. First-time buyers respond strongly to perceived friendliness and context. Practical recommendations suggest that bakery owners enhance loyalty through personalised service, sensory environments, and culturally relevant branding. Socially, these bakeries act as meaningful community spaces that support cultural continuity and emotional well-being. Although the study offers valuable insights into emotional behaviour in Northern bakeries, its single-region, qualitative focus limits wider applicability; future research should involve larger samples and comparative settings. This research is distinctive because, it highlights the overlooked emotional dimensions of consumer behaviour in local Sri Lankan microenterprises.
Keywords: Emotional triggers; psychological insights; Qualitative approach; Sensory environments; Thematic analysis